2022
DOI: 10.3390/ijms23031198
|View full text |Cite
|
Sign up to set email alerts
|

Myo-Inositol Limits Kainic Acid-Induced Epileptogenesis in Rats

Abstract: Epilepsy is a severe neurological disease characterized by spontaneous recurrent seizures (SRS). A complex pathophysiological process referred to as epileptogenesis transforms a normal brain into an epileptic one. Prevention of epileptogenesis is a subject of intensive research. Currently, there are no clinically approved drugs that can act as preventive medication. Our previous studies have revealed highly promising antiepileptogenic properties of a compound–myo-inositol (MI) and the present research broadens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Using electrophysiological method, Gamkrelidze et al found that myo-inositol has a significant local seizure-suppressant effect [5]. In a recent study, several favorable effects of myo-inositol were observed in rat models, including decreasing the frequency and duration of electrographic spontaneous recurrent seizures in the hippocampus, ameliorating epileptogenesis-related spatial learning and memory deficit, and alleviating cell loss in the hippocampus [7]. Phosphoinositide signaling pathway and myoinositol action on gamma amino butyric acid-A receptors were the possible mechanisms of this protective effect [, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using electrophysiological method, Gamkrelidze et al found that myo-inositol has a significant local seizure-suppressant effect [5]. In a recent study, several favorable effects of myo-inositol were observed in rat models, including decreasing the frequency and duration of electrographic spontaneous recurrent seizures in the hippocampus, ameliorating epileptogenesis-related spatial learning and memory deficit, and alleviating cell loss in the hippocampus [7]. Phosphoinositide signaling pathway and myoinositol action on gamma amino butyric acid-A receptors were the possible mechanisms of this protective effect [, 45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there is a lot of research into the potential link between metabolites and epilepsy, implying that certain metabolites are involved in the development of epilepsy. Myoinositol, for instance, has been shown in experimental experiments to have a seizure-suppressing impact, indicating a potential protective role for myo-inositol in epilepsy [5,6,7]. In addition, the term "metabolic epilepsy" has been proposed by the International League Against Epilepsy (ILAE) organization, which has identified numerous metabolic issues in relation to epilepsy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Various conditions have been reported to benefit from MI treatment, such as depressive disorders ( Taylor et al, 2004 ), and polycystic ovary syndrome ( Unfer et al, 2017 ). Moreover, antiepileptogenic properties of MI have been shown in our previous studies performed on pharmacological (kainic acid-KA) animal models of epilepsy ( Kandashvili et al, 2022 , Tsverava et al, 2019 , Tsverava et al, 2016 ). It should be emphasized that MI has a long-term influence on KA-induced alterations since its beneficial effects are maintained for at least 1 month after its treatments end ( Kandashvili et al, 2022 , Tsverava et al, 2019 ).…”
Section: Introductionmentioning
confidence: 69%
“…12,13 Using this model, myo-inositol administered 4 h after KA injection and continued for 4 weeks reduced the occurrence and duration of SRSs without affecting the onset of epilepsy, thus documenting a disease-modifying effect independent of any activity on epileptogenesis. 14 Interestingly, this result was ascribed to the modulation of GABA A receptors, which notoriously are potentiated by neurosteroids such as allopregnanolone and pregnanolone, whereas pregnenolone sulfate displays opposite properties. 7 Other, different mechanisms could also be involved in the modification of epilepsy in KA-treated rats, for instance, neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The KA model represents a very useful tool to investigate epileptogenesis and the progression of epilepsy after brain damage 12,13 . Using this model, myo‐inositol administered 4 h after KA injection and continued for 4 weeks reduced the occurrence and duration of SRSs without affecting the onset of epilepsy, thus documenting a disease‐modifying effect independent of any activity on epileptogenesis 14 . Interestingly, this result was ascribed to the modulation of GABA A receptors, which notoriously are potentiated by neurosteroids such as allopregnanolone and pregnanolone, whereas pregnenolone sulfate displays opposite properties 7 …”
Section: Discussionmentioning
confidence: 99%